2020
DOI: 10.1038/s41467-020-16647-1
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-resistant metal-organic framework enables efficient separation of krypton fission gas from spent nuclear fuel

Abstract: Capture and storage of volatile radionuclides that result from processing of used nuclear fuel is a major challenge. Solid adsorbents, in particular ultra-microporous metal-organic frameworks, could be effective in capturing these volatile radionuclides, including 85 Kr. However, metal-organic frameworks are found to have higher affinity for xenon than for krypton, and have comparable affinity for Kr and N 2. Also, the adsorbent needs to have high radiation stability. To address these challenges, here we evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 41 publications
4
66
0
Order By: Relevance
“…CHA zeolite without any impurity phase was identified from PXRD patterns (Figure 5 c). In contrast, phase changes were observed for MOF SIFSIX‐3 at 1 kGy [12a] and nickel formate was identified for MOF NiDOBDC at 67.2 kGy [42] . For current benchmark SAPO‐34 zeolite membranes, the separation performance dropped by 36.6 % over 60 days storage and irradiation under atmosphere conditions [20] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CHA zeolite without any impurity phase was identified from PXRD patterns (Figure 5 c). In contrast, phase changes were observed for MOF SIFSIX‐3 at 1 kGy [12a] and nickel formate was identified for MOF NiDOBDC at 67.2 kGy [42] . For current benchmark SAPO‐34 zeolite membranes, the separation performance dropped by 36.6 % over 60 days storage and irradiation under atmosphere conditions [20] .…”
Section: Resultsmentioning
confidence: 99%
“…The reported polycrystalline membranes for Kr/Xe separation, such as SAPO‐34, [16a–d] are extremely sensitive to moisture because channel blockage [17] and framework collapse [18] occurred through water uptake from off‐gas streams [19] . Sufficient resistance to γ‐radiation is another essential criterion for practical application using radioactive 85 Kr, [12a] but the radiation stability of polycrystalline membranes is hardly reported [20]…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, extensive research has been done to adopt physisorption with suitable absorbents to capture and separate Xe and Kr at or near room temperature for the advantages of low cost, high efficiency, and reliability. 1,7 Currently, activated carbon, 8-10 zeolites, [11][12][13][14] and metalorganic frameworks (MOFs) 15,16 have drawn great attention for the high-efficient separation of Xe and Kr by adsorption. However, there is always a major challenge to efficiently capture the trace noble gases from the gas mixture because of their chemical inertness and small size difference with nitrogen (kinetic diameter: Kr, 3.65 Å; N 2 , 3.84 Å; Xe, 4.04 Å).…”
Section: Introductionmentioning
confidence: 99%
“…SIFSIX-3-Cu showed a dynamic selectivity of 4.81 with Xe/Kr and 24.38 with Kr/N 2 in dry air, which could endure 50 kGy b and g irradiation. 42,43 Yan et al reported a series of Zr-Fum MOF and UiO-66(Zr), the Zr-Fum-Me possessed a Henry's selectivity of 14.8 with a dose of 8 kGy gray irradiation resistant, UiO-66(Zr) owns a similar structure to that of Zr-Fum with a Xe/Kr selectivity of 7.7 and 2 kGy g irradiation resistance. 44,45 Cerium is a rare-earth metal in the lanthanide class possessing advantages of affordability and accessibility in nature.…”
Section: Introductionmentioning
confidence: 99%